Techno-economic evaluation of integrated levulinic acid, formic acid, and furfural plant from oil palm empty fruit bunch with pre-treatment variations - Denia Apriliani RAHMAN; Andre Fahriz Perdana HARAHAP; Misri A GOZAN (E-Journal Menara Perkebunan, 2022)
AbstractLevulinic acid, a platform biochemical, might be utilized as a biodiesel additive in biodiesel production. Global demand for levulinic acids was 3,820 tons in 2020, while the roadmap target of biodiesel in Indonesia will reach 20% of diesel consumption in 2016-2025. These figures become the considerations for establishing the levulinic acid plant in Indonesia. The study's focus analyzed the economic viability of integrated levulinic acid production plant design based on Oil Palm Empty Fruit Bunches (OPEFB) in Indonesia. OPEFB was selected as raw material due to the enormous solid waste generated by oil palm plantations. In the plant design, software SuperPro Designer 9.0's used as a process tool simulator. The economic analysis showed the Net Present Value (NPV) as the US $ 548,850,764, an Internal Rate of Return (IRR) of 24.75%, and a payback period (PBP) estimated within six years with a Minimum Attractive Rate Return (MARR) of 6.1%. The optimal production capacities of levulinic acid, furfural, and formic acid are 12,425; 15,105 and 6,074 tonnes/year.[Keywords: cellulose, delignification, levulinic acid, OPEFB, simulation] AbstrakAsam levulinat, sebuah platform biokimia, dapat digunakan sebagai aditif biodiesel dalam produksi biodiesel. Permintaan global asam levulinat mencapai 3.820 ton pada 2020, sedangkan roadmap target biodiesel di Indonesia mencapai 20% dari konsumsi solar pada 2016-2025. Angka-angka ini menjadi pertimbangan untuk mendirikan pabrik asam levulinat di Indonesia. Fokus penelitian menganalisis kelayakan ekonomi rancangan pabrik produksi asam levulinat terpadu berbasis Tandan Kosong Kelapa Sawit (TKKS) di Indonesia. TKKS dipilih sebagai bahan baku karena limbah padat yang dihasilkan perkebunan kelapa sawit sangat besar. Dalam perancangan pabrik, software SuperPro Designer 9.0 digunakan sebagai alat simulator proses. Analisis ekonomi menunjukkan Net Present Value (NPV) sebesar US$ 548.850.764, Internal Rate of Return (IRR) 24,75%, dan payback period (PBP) diperkirakan dalam enam tahun dengan Minimum Attractive Rate Return (MARR) 6,1%. Kapasitas produksi optimal asam levulinat, furfural dan asam format masing-masing adalah 12.425; 15.105 dan 6.074 ton/tahun.[Kata kunci: selulosa, delignifikasi, asam levulinat, TKKS, simulasi]